Effectiveness of Pjbl-Based E-LKPD Implementation in Teaching Plant Tissue Materials - Rahiimah, Natasya; Fitri, Rahmadhani; Yogica, Relsas (Biotik, 2025)
This development research was conducted based on the difficulties faced by teachers. The aim of this research is to produce an e-LKPD that is valid, practical, effective, and appealing for students in the subject of plant tissues. The applied learning model is expected to assist teachers in creating engaging learning media. This research employs the Systematic Literature Review (SLR) method as its research methodology. This involves selecting each relevant journal or prior study and compiling their results as references for the model or idea to be developed. The study involves collecting information and data from reliable sources such as international scientific journals, seminar proceedings, research reports, and reference books. The data in this research consists of a literature review of previous studies sourced from journals published between 2020 and 2024. From several scientific articles that were examined and compared, it can be concluded that several studies using simulation models in their learning processes have been successfully implemented and applied to both students and teachers, at the elementary school and vocational high school levels.